Possibilities within Acceptance and Commitment Therapy for Approaching Moral Injury - A. Nieuwsma, Jason; D. Walser, Robyn; K. Farnsworth, Jacob; D. Drescher, Kent; G. Meador, Keith; Nash, William (Current Psychiatry Reviews, 2015)
Moral injury and acceptance and commitment therapy (ACT) are both topics that have only quite recently been introduced into the mental health literature. Although inquiries into these two domains have been advanced independent from one another, both challenge various aspects of the traditional medical model for diagnosing, understanding, and treating psychiatric problems. This article explores complementary possibilities for using ACT to approach the care of persons with moral injury. Descriptions of moral injury and ACT are provided along with an overview of the developmental histories and relevant research literature in each of these domains. Specific possibilities for attending to moral injury are explored via examination of each of the six core processes in ACT: acceptance; cognitive defusion; contact with the present moment; self-as-context; values; and committed action. It is suggested that ACT has unique potential as an evidence-based psychotherapy for approaching numerous moral injury related issues. These include: understanding human suffering as normative, expectable, and potentially meaningful; balancing both verbal and experiential understandings of morality; fostering forgiveness in a manner that is not dismissive of guilt but employs it to orient towards values; holding and honoring morally injurious experiences in a way that respects and empathizes with ongoing suffering; identifying a sense of self from which to behaviorally enact valued actions; and inviting engagement from care providers and communities outside of the traditional mental health care system. Future conceptual and empirical work is needed, including studies examining the efficacy and effectiveness of ACT for moral injury.
Keywords: social-functional